Analisis Modal Sosial Pedagang Di Pasar Tradisional Di Desa Tanggul Wetan, Kec. Tanggul, Kab. Jember - Manie Sari Ama Putri; Puteri Adiba Wan Noer Azizah; Dhea Amallia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Traditional markets are transaction centers and supply networks for people's basic needs so that in traditional markets there is quite strong competitiveness between traders because in traditional markets many traders sell the same merchandise as other traders. Therefore, in serving consumers, traders must provide good service so that consumers feel comfortable and will return and become regulars at the shop. In traditional markets there is a relationship or personality relationship between sellers and buyers. This is related to the concept of social capital which is getting to know each other and in which there are also elements of trust, social networks and normative values ​​between economic actors. Social capital in traditional markets plays a very important role in the existence of traditional markets so it is not surprising that the development of modern markets is increasingly widespread nowadays, but traditional markets can still survive and become a culture and necessity that is still very much needed by the local community to this day. The research method for analyzing Trader Interactions in Traditional Markets to Improve Economic Welfare in Tanggul Wetan Village uses descriptive methods. In this research analysis, we use social capital theory based on Pierre Bourdieu's perspective, which states that the definition of social capital is the amount of resources, actual or virtual, that are gathered in an individual or group because they have a long-lasting network of reciprocal relationships of acquaintance and more or less recognition. institutionalized (Field, 2011:23). We researchers use the concept of trust.